‘Unburden us and them’: encountering ‘the other’ in meetings between Bosnian genocide survivors and Dutch UN veterans - Driessen, Siri; van Brenk, Jeannette; Immler, Nicole L.; Vermetten, Eric (Frontiers in Sociology, 2025)
Recently, the Dutch government granted ‘Dutchbat 3’ veterans and their partners the opportunity to return to Srebrenica and its surroundings, where they had been located up until the genocide of 1995. An important part of these return trips is dedicated to on-site meetings with women survivors of war and genocide. These encounters are thought to encourage more dialogue, mutual understanding, and an engagement with ‘the other’s’ points of view, with the aim of transforming the relationship between the participants. However, the conditions needed to make these encounters equal and meaningful are not yet fully understood. Levelling the playing field in encounters implies an ‘unlearning’ of earlier acquired perspectives, narratives, and worldviews, and involves mutual openness and respect. The success of an encounter is dependent on the willingness of visitors and hosts to think and do differently. This might be challenging in a context in which the memory of past conflict is highly gendered, polarized and politicized. By better grasping whether and in what ways encounters with ‘the other’ might become meaningful, it could be possible to design and implement these encounters accordingly. In this article, we aim to identify the conditions needed to enable or disable such encounters. Based on ethnographic research of survivors and veterans, we ask: which conditions need to be met to make the encounters meaningful for the participants? We argue that their current form has potential, but that, to be successful, more attention is needed to better understand what engaging with ‘the other’ really requires: it means being ready to ‘restory’ the past and be open to different perspectives. Our research shows that this is not easily done: dominant narratives feed into dichotomous memory cultures, causing people to fall back into old patterns, despite the fact that both groups had suffered from very similar forms of institutional neglect. To redress this the conceptualization of the encounters and return trips would need to be carefully considered.